The Implementation of Interactive Multimedia With Macromedia Flash 8.0 in Biological Learning at SMK Ibrahimy 2 Sukorejo - Dyan Yuliana; Achmad Fauzan Azzubair (Universitas Negeri Padang, 2020)
Implementation of computer applications such as GSP, Adobe Flash CS 4, Macromedia Flash 8.0, and others as an interactive and efficient learning media is something that must be done in order to improve the quality of the process and the results of learning. Included in SMK Ibrahimy 2 Sukorejo the application of technology media in absolute learning is done in order to achieve the expected quality of education and learning outcomes, especially in subjects / materials / learning objects that are difficult to present in the classroom, such as in Biology, which requires not only delivered through stories but through evidence that can be presented in a concrete manner can be seen in front of students, then using the Macromedia Flash 8.0 application media is expected to increase the achievement of competencies expected in each Indicator. This study aims to apply learning media with systematic steps in accordance with the rules in applying the learning media of Biology Vocational High School class X using the Macromedia Flash 8.0 Program and knowing the feasibility of the developed Information and Communication Technology learning media software. This research is a development research conducted with four main stages namely: analysis, design, production and evaluation. The results show that: (1) This learning media has gone through the systematic steps of development research which include the stages of: analysis, design, production and evaluation. (2) the quality of instructional media is based on the results of trials on the intended students in both categories with an average score of 3.7. Thus it can be concluded that this Biology learning media product has fulfilled the rules of research and application and is effectively used in the learning process for students of class X SMK Ibrahimy 2 Sukorejo. Keywords : Interactive Multimedia, Macromedia Flash 8.0, Biology Learning.